2021
DOI: 10.1088/1674-4527/21/11/288
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of 2716 hot emission-line stars from LAMOST DR5

Abstract: We present a catalog of 3339 hot emission-line stars (ELSs) identified from 451 695 O, B and A type spectra, provided by LAMOST Data Release 5 (DR5). We developed an automated Python routine that identified 5437 spectra having a peak between 6561 and 6568 Å. False detections and bad spectra were removed, leaving 4138 good emission-line spectra of 3339 unique ELSs. We re-estimated the spectral types of 3307 spectra as the LAMOST Stellar Parameter Pipeline (LASP) did not provide accurate spectral types for these… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 86 publications
0
9
0
Order By: Relevance
“…These statistics, summarised in Table 2, 2021) with mass determinations. However, other less famous objects of the class do exist in the literature, like the recently proposed 58 Herbig Ae/Be sources from the LAMOST survey (Shridharan et al 2021;Zhang et al 2021), the 13 proposed Herbig Ae/Be stars in the Small Magellanic Cloud (Keller et al 2019), or the 77 IMTTs found in the Carina Nebula (Nuñez et al 2021).…”
Section: General Remarksmentioning
confidence: 99%
“…These statistics, summarised in Table 2, 2021) with mass determinations. However, other less famous objects of the class do exist in the literature, like the recently proposed 58 Herbig Ae/Be sources from the LAMOST survey (Shridharan et al 2021;Zhang et al 2021), the 13 proposed Herbig Ae/Be stars in the Small Magellanic Cloud (Keller et al 2019), or the 77 IMTTs found in the Carina Nebula (Nuñez et al 2021).…”
Section: General Remarksmentioning
confidence: 99%
“…For 686 stars in the LEMC, we could not estimate the spectral type due to the low signal-to-noise ratio (S/N) in the bluer region of the LAMOST spectra. Due to the observation strategy of LAMOST DR5, the majority of our sample is towards the galactic anti-centre direction (Figure 1 of Shridharan et al 2021). Limited photometric survey footprints towards this region inhibited us from studying these stars photometrically or using SEDs to estimate their stellar parameters.…”
Section: Synthetic Photometry From Bp/rp Spectramentioning
confidence: 99%
“…Recently, the study of these objects benefited greatly from the advent of large-scale spectroscopic surveys (e.g. Chojnowski et al 2015;Anusha et al 2021;Zhang et al 2022;Shridharan et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…This is particulary helpful for the identification of (cool) objects that do not show conspicuous Balmer-line profiles, let alone any appreciable Balmer-line emission. However, most recent surveys that target emission-line and shell stars specifically search for emission signatures in the Hα line (Anusha et al 2021;Zhang et al 2022;Shridharan et al 2021), and these objects will consequently be missed.…”
Section: Introductionmentioning
confidence: 99%